Determinants of quit attempts among current Indian tobacco users: Findings from global Adult tobacco survey, 2016-17 - Varsha Nair; Sneha D. Mallya; Akhilesh Kumar Pandey; Prashant Kumar Singh; Amit Yadav; Muralidhar M. Kulkarni (Elsevier, 2023)
Problem considered: Tobacco use is the second most common preventable cause of death in the world and quitting tobacco is an important strategy to prevent premature morbidity and mortality. The objective of this study was to determine the correlates of quit attempts among tobacco users in India from GATS-2 data. Methods: Complex sample analysis was considered for logistic regression analysis to identify the correlates of quit attempts using Global Adult Tobacco Survey (GATS)- 2 (2016-17) data. Weighted estimates were calculated for sample statistics. Results: A marked difference was observed in quit attempt rates across various states of India (p < 0.001). The quit attempt rate among current smokers and smokeless tobacco users was 33.7% [95% confidence interval (CI) = 32.8-34.7] and 28.9% [95% CI = 28.1-29.6] in India as per GATS 2. Individuals from scheduled caste and other backward classes had higher odds of making a quit attempt among current smokers. Among the smokeless tobacco users (SLT), factors namely age, belonging to other backward classes and having a belief that tobacco use is dangerous to health were independently associated with quit attempts. Majority of the users, 83.5% (95%CI = 82.2-84.8) of the smokers and 88%(95%CI = 87.0-88.9) of the SLT users made a quit attempt without any cessation aid. Conclusion: Formulating tobacco control policies specific to the groups identified may bridge the gap between tobacco users and cessation services. The varying quit attempt rates reported across the country necessitates stringent implementation of tobacco control policies and programmes.